Biological and targeted-synthetic disease-modifying anti-rheumatic drugs with concomitant methotrexate or leflunomide in rheumatoid arthritis: real-life TReasure prospective data - Kimyon, G.; Kalyoncu, U.; Kiraz, S.; Bes, C.; Coskun, N.; Yagiz, B.; Ertenli, I (Clinical & Exper Rheumatology, 2021)
Objective To determine the real-life efficacy, safety, and drug-retention rates of leflunomide (LEF) or methotrexate (MTX) as a synthetic DMARD used in combination with biological DMARDs for rheumatoid arthritis (RA). Methods The TReasure database is a web-based, prospective, observational cohort of RA and spondyloarthritis patients from 17 centres in different regions of Turkey and data entry was enabled since December 2017. Until May 2019,2556 RA patients on biologic treatment were recorded. Demographic and RA-related data of 1526 patient either received LEF or MTX were compared, efficacy of both drugs compared by RA-disease activity composite indices. Reasons fordrug discontinuation also recorded. Drug retention rates were compared with Kaplan-Meier curves (log-rank test). Results Of 2556 RA patients 1526 (59.7%) were receiving concomitant LEE (n=646, 42 3%; median follow up 35 months) or concomitant MTX (n=880, 573%; median follow-up 32 months) at the time of initiation to their first bDMARDs. The LEE group were older and had longer disease duration, proportion of females and seropositive patients was higher in this group. In the LEE group, non-anti-TNF agents were used in higher rate. Remission rates, changes in composite indices and rate of comorbidities and adverse events were similar in both groups. The retention rate of LEE + non-anti-TNF b/tsDMARDs was higher compared to MTX + anti-TNF bDMARDs (p=0.002, log-rank). Rates of adverse events were similar in both groups. Conclusion LEE in combination with either anti TNF or non anti DIF drugs appears as an effective and safe therapeutic option at least as MIX.
Keywords: leflunomide; methotrexate; rheumatoid arthritis; biologic or targeted-synthetic DMARDs